Variation in adenoma detection rate and the lifetime benefits and cost of colorectal cancer screening: A microsimulation model - Meester, R.; Doubeni, C.; Lansdorp-Vogelaar, Iris; Jensen, C.; Van Der Meulen, M.; Levin, T.; Quinn, V.; Schottinger, J.; Zauber, A.; Corley, D.; Van Ballegooijen, M. (2015)
Importance: Colonoscopy is the most commonly used colorectal cancer screening test in the United States. Its quality, as measured by adenoma detection rates (ADRs), varies widely among physicians, with unknown consequences for the cost and benefits of screening programs. Objective: To estimate the lifetime benefits, complications, and costs of an initial colonoscopy screening program at different levels of adenoma detection. Design, Setting, and Participants: Microsimulation modeling with data from a community-based health care system on ADR variation and cancer risk among 57 588 patients examined by 136 physicians from 1998 through 2010. Exposures: Using modeling, no screening was compared with screening initiation with colonoscopy according to ADR quintiles (averages 15.3%, quintile 1; 21.3%, quintile 2; 25.6%, quintile 3; 30.9%, quintile 4; and 38.7%, quintile 5) at ages 50, 60, and 70 years with appropriate surveillance of patients with adenoma. Main Outcomes and Measures: Estimated lifetime colorectal cancer incidence and mortality, number of colonoscopies, complications, and costs per 1000 patients, all discounted at 3%per year and including 95%confidence intervals from multiway probabilistic sensitivity analysis. Results: In simulation modeling, among unscreened patients the lifetime risk of colorectal cancer incidence was 34.2 per 1000 (95%CI, 25.9-43.6) and risk of mortality was 13.4 per 1000 (95%CI, 10.0-17.6). Among screened patients, simulated lifetime incidence decreased with lower to higher ADRs (26.6; 95%CI, 20.0-34.3 for quintile 1 vs 12.5; 95%CI, 9.3-16.5 for quintile 5) as did mortality (5.7; 95%CI, 4.2-7.7 for quintile 1 vs 2.3; 95%CI, 1.7-3.1 for quintile 5). Compared with quintile 1, simulated lifetime incidence was on average 11.4%(95%CI, 10.3%-11.9%) lower for every 5 percentage-point increase of ADRs and for mortality, 12.8% (95%CI, 11.1%-13.7%) lower. Complications increased from 6.0 (95%CI, 4.0-8.5) of 2777 colonoscopies (95%CI, 2626-2943) in quintile 1 to 8.9 (95%CI, 6.1-12.0) complications of 3376 (95%CI, 3081-3681) colonoscopies in quintile 5. Estimated net screening costs were lower from quintile 1 (US $2.1 million, 95%CI, $1.8-$2.4 million) to quintile 5 (US $1.8 million, 95%CI, $1.3-$2.3 million) due to averted cancer treatment costs. Results were stable across sensitivity analyses. CONCLUSIONS AND RELEVANCE: In this microsimulation modeling study, higher adenoma detection rates in screening colonoscopy were associated with lower lifetime risks of colorectal cancer and colorectal cancer mortality without being associated with higher overall costs. Future research is needed to assess whether increasing adenoma detection would be associated with improved patient outcomes.